SAT0234 Counting Costs Under Severe Financial Constraints: A Cost of Illness Analysis of Spondyloarthropathies in Greece. (9th June 2015) - Tsifetaki, N.; Migkos, M.P.; Papagoras, C.; Voulgari, P.V.; Athanasakis, K.; Drosos, A.A.
Abstract : Objectives: To investigate the total annual direct cost of patients with spondyloarthropathies (SpA) in Greece. Methods: Retrospective study of 156 SpA patients fulfilling Assessment of SpondyloArthritis International Society (ASAS) classification criteria who were followed up regularly in the rheumatology clinic of University hospital of Ioannina. Sixty four had ankylosing spondylitis (AS) according to modified New York criteria and 92 psoriatic arthritis (PsA) according to classification criteria for psoriatic arthritis (CASPAR). Health resource use for each patient was elicited via a retrospective chart review which documented the use of monitoring visits, medications, laboratory/diagnostic tests and inpatient stays for the previous year from the date that the review took place. Costs were calculated from a third party payer perspective, and are reported in year 2014 Euros. Results: The mean ± SD annual direct cost for the patients with SpA reaches € 8680±6627. For the patients with PsA and AS the cost is estimated to be approximately € 8097±6802 and € 9531±6322 respectively. Major cost drives were the cost of medications which represent 88.9%, 88.2% and 89.3% of the mean total direct cost for SpA, AS and PsA respectively. The total annual pharmaceutical expenditures for these patients reach the amount of € 7717±6615. Of the latter, 97.1% (€ 7499±6607) is the cost of the treatment with biologic DMARDs and only 2.8% (€ 218±455) is the cost of the annual non biologic pharmaceutical expenditures. The annual amount of the scheduled tests for all patients corresponds to 7.5% and for those performed on emergency basis 1.1% of the mean annual direct cost. Furthermore the cost for scheduled and emergency hospitalization as well as the cost of scheduled visits in outpatient clinic corresponds to 2.5% of the mean total annual direct cost for the patients with SpA. Conclusions: The SpA carries substantial financial cost, especially in the era of new treatment options. Adequate access and treatment for SpA patients remains a necessity, even under the light of fiscal constraints. Disclosure of Interest: None declared